Aplicação de novos catalisadores suportados com óxido de cálcio e magnésio na obtenção de carbonato de glicerol - Ferreira, Jonny Erick dos Santos (2017)
Therefore, this research proposes the glycerol transformation in a product with a larger value aggregated the glycerol carbonate. For this, catalysts were synthesized under the influence of modified alumina with calcium and magnesium, produced by methods of polymeric precursors and impregnating in a wet system. The X-ray diffraction (XRD), Fourier transform infrared (FTIR), Scanning electron microscopy and dispersive energy spectrometry (SEM-EDS) and X-ray fluorescence spectroscopy (FRX). The glycerol reaction with the dimethyl carbonate was processed in 95º C, with 3.5 dimethyl carbonate/glycerol and 20% of the mass of the catalyst relative to glycerol. The sprectroscopic analysis in the infared region of the reactional product suggested the formation of the carbonyl group (C = O), vibrational mode in the region 1770cm-1 , what is characteristic of a glycerol carbonate Chromatograms confirmed the formation of glycerol carbonate. The conversion values of carbonation of the glycerol with the Al-Ca01 and Al-Ca02 catalysts were 96.5 and 68.6%, respectively, whereas for Al-Mg01 and Al-Mg02, 50.9 and 39.6%, respectively, noting that the conversion potential of glycerol to glycerol carbonate followed the sequence Al-Ca01 <AlCa02 <Al-Mg01 <Al-Mg02. It was observed the formation of glycidol as a minor product. It was fullfilled a 24 factorial planning to evaluate the efects of the variables, composition of the catalyst, molar ration between glycerol and dimethyl carbonate, time and temperature on the reaction of the formation of the glycerol carbonate and determine if the ideal conditions of the process for better results of conversion and selectivity.